Diet of Snow Leopard Panthera uncia in Kanchanjunga Conservation Area (ZOO-Journal, 2021)
The population of Snow Leopard is declining due to anthropogenic activities and prey scarcity. Snow Leopard’s preferred prey species are Tibetan Argali, Blue Sheep, Himalayan Tahr, Himalayan Marmot, Royle’s Pika, rodents, and livestock such as Yak, Horse, Lulu Cow, Goat and Sheep. Due to livestock depredation by Snow Leopards and other carnivores, local people have a negative attitude towards carnivores’ conservation leading to retaliatory killing. This study identified whether Snow Leopards prey on wildlife or livestock based on micro-histological study of Snow Leopard’s scats. Micro-histological analysis of 39 scat samples of Snow Leopard confirmed that Blue Sheep is the major prey species in Kanchanjunga Conservation Area (KCA). The scat analysis also showed that Snow Leopards prey on livestock mainly to Chauri in KCA, however the number and incidences were few. The herders also confirmed the occasional hunting of their livestock depredation by Snow Leopard in KCA. People have positive attitudes towards Snow Leopard conservation because they are less suffering from Snow Leopard in KCA. If wild prey species are abundant in the wild, livestock depredation might be low.